Utilization of Cassava Starch in Copolymerisation of Superabsorbent Polymer Composite (SAPC) - Abidin, Akhmad Z.; Puspasari, Tiara; Graha, Hafis Pratama Rendra (Journal of Engineering and Technological Sciences, 2014)
Cassava starch was used as the main chain in the copolymerization of a superabsorbent polymer composite (SAPC) based on acrylic acid and bentonite. The SAPC was synthesized through graft polymerization using nano-sized bentonite as reinforcement. The variables in this experiment were: bentonite concentration, acrylic acid to starch weight ratio, concentration of initiator, and cross linker. The product was characterized using FTIR, SEM and TGA-DSC. The results show that the polymerization reactions involved processes of incorporating starch chains as polymer backbone and grafting acrylic acid monomers onto it. The use of cassava starch in the polymerisation produced a very short reaction time (10-15 minutes), which led to SAPC production with higher efficiency and lower cost. Bentonite interacts with monomers via hydrogen and weak bonding, thus improving the thermal properties of the product. The maximum absorbance capacity obtained was at an acrylic acid to starch weight ratio of 5 and a concentration of initiator, cross linker and bentonite of 0.5, 0.05 and 2 weight percent, respectively. The product is suitable for agricultural and medical applications as well as common superabsorbent polymer applications.